Perceived leadership practices and organizational commitment of consulting engineers at their working place - Tan, Ooi Kuan (2014)
The objectives of this study are to examine the issues confronting consulting engineers. The issues are: (a) the relationship between perceived leadership practices and consulting engineer's organizational commitment in their working place and, (b) the differences of consulting engineers’ organizational commitment based on gender, age and years of working experience. This study leverages on (a) Kouzes and Posner’s five perceived leadership practices (1987), and (b) Mowday, Porter and Steers’ organizational commitment (1979). This study was specifically addressed to 387 respondents who worked with consulting firms registered under the Association of Consulting Engineers, Malaysia (ACEM). The random sampling technique was used and a self-administered survey was performed for this research which included a set of questionnaires consisting of sections on personal information, leadership practices index (LPI) and organizational commitment (OCQ). The quantitative research method was used for data analysis. Firstly, it involved using the Spearman-rho correlation analysis to examine the relationship between the consulting engineers’ perceived leadership practices and organizational commitment at their work place. Secondly, the Kruskal Wallis test was used to investigate the differences between the consulting engineers’ organizational commitment based on age and years of experience. Thirdly, the Wilcoxon Signed Rank test was used to investigate the differences between the consulting engineers’ organizational commitment based on gender. The findings revealed that the five perceived leadership practices have significant relationships between perceived leadership practices and the consulting engineers’ organizational commitment at their work place. Another finding revealed that there is a significant difference between the consulting engineers’ organizational commitment based on gender, and age, and years of working experience. The findings contribute to the knowledge that consulting engineers’ organizational commitment is positively related to the engineering superior’s leadership skills of coaching, leading and guiding consulting engineers to achieve the same goal